Analisis Cost Volume Profit (CVP) sebagai alat perencanaan laba - Rohmah, Firda Yusnafa; Wicaksono, Achmad; Muzakki, Kafidin; Fahriani, Dian (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
Vaname shrimp farming has great economic potential, but fluctuating production costs and market prices pose challenges. This study analyzes Cost Volume Profit (CVP) as a profit planning tool in determining Break Even Point (BEP), Contribution Margin (CM), and Margin of Safety (MoS) to optimize production and cost strategies. CVP acts as an analytical tool that assists in managing costs, determining production targets, and setting pricing strategies. Its application allows businesses to improve efficiency, profitability, and business sustainability. The method used is descriptive qualitative. The analysis technique is CVP. Financial data for 2023-2024 was obtained through observation, interviews, and documentation. The results show that production in 2023 has not met BEP, causing losses. However, in 2024, production increased, while BEP fell, so the business began to make a profit. MoS increased, and CM increased. Cost efficiency played an important role, with variable costs per kg decreasing in 2024, supported by greater pond maintenance expenditure in 2023. In addition to CVP, other X factors also improved profitability. Projections for 2025 target an increase in production capacity and a decrease in BEP, resulting in an expected increase in profit.